2023
DOI: 10.22610/imbr.v15i1(i)si.3387
|View full text |Cite
|
Sign up to set email alerts
|

A Blessing in Disguise: Covid-19 Pandemic and the Emergence of E-Payment

Abstract: E-payment offers efficiency in terms of speed, security, convenience, and cost, especially during this pandemic. The study involves monthly data that spans from January 2016 to June 2021. This study aims to investigate selected payment channels and instruments' influence on retail e-payment transactions. The study is also interested to examine the interaction effects of Covid-19 on the relationship between credit card usage and retail e-payment transaction. The study employs Newey-West standard error regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…(1) Descriptive analysis is presented in table 1 where it can be seen that before covid-19 the average weekly use of e-payments was 7.17 times and that usage increased by 82.67% to reach 13.1 times per week and that is in line with the literature as stated by Ahmad et al (2023), Khan et al (2021), Al-Dmour et al (2021), and many others. Using kurtosis and skewness results to identify distribution normality of the data, it can be seen that both of them fall within the acceptable range of normal distribution since the data fall between ±3 and ±10 for skewness and kurtosis respectively (Klein, 1998).…”
Section: Research Methodology and Empirical Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…(1) Descriptive analysis is presented in table 1 where it can be seen that before covid-19 the average weekly use of e-payments was 7.17 times and that usage increased by 82.67% to reach 13.1 times per week and that is in line with the literature as stated by Ahmad et al (2023), Khan et al (2021), Al-Dmour et al (2021), and many others. Using kurtosis and skewness results to identify distribution normality of the data, it can be seen that both of them fall within the acceptable range of normal distribution since the data fall between ±3 and ±10 for skewness and kurtosis respectively (Klein, 1998).…”
Section: Research Methodology and Empirical Resultssupporting
confidence: 69%
“…Covid-19 lockdowns forced those consumers to overcome their fears toward financial technology and start exploring it. Ahmad et al (2023), showed that covid-19 significantly influenced the emergence of e-payment in Malaysia and that internet banking usage and e-commerce showed great potential during the pandemic with a substantial increment since 2020. Khan et al (2021), stated that as a result of covid-19 pandemic limited mobility the usage of e-payment methods increased dramatically.…”
Section: Introductionmentioning
confidence: 99%